2019
DOI: 10.1016/j.petrol.2019.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically associating polymers for enhanced oil recovery – Part A: A review on the effects of some key reservoir conditions

Abstract: Research advancement in polymer flooding for Enhanced Oil Recovery (EOR) has been growing over the last decade. This growth can be tied to increased funding towards the development of superior polymers such as hydrophobically associating polymers when oil prices were high and increasing concern that "easy oil" has been exploited with the focus now on "difficult to extract" oil. The use of hydrophobically associating polymers for EOR was discussed along with its limitations. In this context, the improved rheolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 166 publications
(277 reference statements)
0
45
0
Order By: Relevance
“…In present work, copolymers PAAI x (x = 7, 10, 15) were prepared by copolymerization of AM, AMPS, and iso-tridecyloxypolyethylene glycol acrylates I13C x AA (x = 7, 10,15), which were prepared from corresponding iso-tridecyloxypolyethylene glycol by esterification with acrylic acid. These polymers were characterized by FTIR, 1 H NMR spectroscopy, and TGA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present work, copolymers PAAI x (x = 7, 10, 15) were prepared by copolymerization of AM, AMPS, and iso-tridecyloxypolyethylene glycol acrylates I13C x AA (x = 7, 10,15), which were prepared from corresponding iso-tridecyloxypolyethylene glycol by esterification with acrylic acid. These polymers were characterized by FTIR, 1 H NMR spectroscopy, and TGA.…”
Section: Discussionmentioning
confidence: 99%
“…As a small fraction of hydrophobic comonomer is incorporated into the polymer backbone, the modified polyacrylamide has improved thickening capability compared to conventional hydrolyzed polyacrylamides; however, such an enhancement in viscosity is significantly dependent on the polymer concentrations, operational shear rate, and conditions of reservoir; this has inhibited the widespread applications of such polymers. [13][14][15] When a surfactant-like monomer is incorporated into polyacrylamide backbone, this modified polyacrylamide has surface activity and is called polymeric surfactant. A lot of studies have shown that compared with hydrolyzed polyacrylamides, polymeric surfactants have a lower molecular weight, stronger temperature and salt resistance, and a certain interfacial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of the backbone of these polymers with hydrophobic comonomers, leads to materials with associative properties, which have improved thickening capabilities under harsh reservoir conditions like high temperature and high salinity. [ 20 ] There are several published reports on obtaining associative polymers with potential application in EOR, [ 21–23 ] where most of them use PAM or polyacrylamide and acrylic acid (PAM / AA) copolymers as the base polymer because of the advantages of having anionic groups in the polymers on their application on sandbanks or native soils. [ 24 ] Another important modification is the use of poly‐(alpha‐alkoxy)acrylamides, since their properties showed good stability in brine solutions for EOR applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, recent studies have focused on the surface modification of the two types of commercial sponges, in order to alter their surface from hydrophilic to hydrophobic for the sponges to have high oil absorption capacity and decent water repellency during the oil/water separation process [44]. Therefore, several materials have been used to switch the hydrophilic sponge surface to hydrophobic, such as silanes [45], hydrophobic polymers [46], hydrophobic nanoparticles [47,48], carbon materials [49][50][51] and various others, making commercial sponges promising candidates for crude oil removal both from seawater (oil spills) and industrial wastewater [52]. Lately, sponges with additional characteristics, such as magnetic properties, stimuli-responsiveness and high durability under harsh conditions, have also been developed in order to be used for the removal of crude oil in more distinct situations [39,40].…”
Section: Introductionmentioning
confidence: 99%